2011
DOI: 10.1530/eje-10-1070
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone- and cortisol-co-secreting adrenal tumors: the lost subtype of primary aldosteronism

Abstract: Current guidelines suggest proving angiotensin-independent aldosterone secretion in patients with primary aldosteronism (PA). It is further recommended to demonstrate unilateral disease because of its consequence for therapy. A general screening for excess secretion of other hormones is not recommended. However, clinically relevant autonomous aldosterone production rarely originates in adrenal tumors, compromised of zona glomerulosa cells only. This article reviews published data on aldosterone-and cortisol-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
109
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(120 citation statements)
references
References 77 publications
4
109
1
4
Order By: Relevance
“…but showing the autonomous secretion of cortisol have been identified as having preclinical (or subclinical) Cushing's syndrome [20,21]. Although the concept of preclinical (or subclinical) CS is not universally accepted [14], Spath et al recently reported that we should consider an APA with co-secretion of cortisol if a patient has 1) PA and an adenoma that is larger than 2.5 cm, 2) cortisol that is non-suppressible with overnight low-dose dexamethasone, or 3) grossly elevated serum levels of hybrid steroids, such as 18-OH-F [22]. In fact, although we did not have a chance to measure serum hybrid steroids, all three cases had a tumor larger than 2.5 cm.…”
Section: Expression Of Steroidogenic Enzymes and Kcnj5 Mrna In Patienmentioning
confidence: 99%
See 1 more Smart Citation
“…but showing the autonomous secretion of cortisol have been identified as having preclinical (or subclinical) Cushing's syndrome [20,21]. Although the concept of preclinical (or subclinical) CS is not universally accepted [14], Spath et al recently reported that we should consider an APA with co-secretion of cortisol if a patient has 1) PA and an adenoma that is larger than 2.5 cm, 2) cortisol that is non-suppressible with overnight low-dose dexamethasone, or 3) grossly elevated serum levels of hybrid steroids, such as 18-OH-F [22]. In fact, although we did not have a chance to measure serum hybrid steroids, all three cases had a tumor larger than 2.5 cm.…”
Section: Expression Of Steroidogenic Enzymes and Kcnj5 Mrna In Patienmentioning
confidence: 99%
“…Hogan et al first reported an aldosterone-and cortisol-producing adenoma in 1977 [23]. Subsequently, several papers have been published regarding the association of PA with the autonomous secretion of cortisol [22,24,25]. Many such reports have come from Japan or Europe.…”
Section: Expression Of Steroidogenic Enzymes and Kcnj5 Mrna In Patienmentioning
confidence: 99%
“…In rare cases, secretion of aldosterone is the main cause of hypertension and optional hypokalemia, and co-secretion of cortisol may play a minor role. Some of the corresponding tumors have been shown to carry activating mutations in the KCNJ5 potassium channel gene that are specific to aldosterone-producing adenomas (15,16,17). Only one study screened for PRKACA mutations in these tumors, but did not report any (7).…”
mentioning
confidence: 99%
“…It should be presumed a diagnosis of bilateral hyperplasia (BAH) is provided in approximately 50 % of patients, whereas in the remaining cases an aldosteroneproducing adenoma (APA) and asymmetrical aldosterone excess is present. Rarer entities include adrenal cortex carcinoma, which occurs in < 1 % of cases [12,13]. Patients with Conn's syndrome have a significantly increased risk of cardiac and vascular diseases, even when compared with patients with similarly poor blood pressure values, but without hyperaldosteronism [14,15].…”
mentioning
confidence: 99%
“…▶ It should likewise be taken into account that larger APAs can also secrete relevant quantities of cortisol such that lateralization due to cortisol co-secretion can no longer be identified computationally [13]. Further, the selectivity index on the contralateral side will be erroneously low.…”
mentioning
confidence: 99%